Preconception preparation of patients with reccurent vulvovaginal candidiasis with the use of immunomodulation therapy - Borovikov I.O; A.S. Avetisian (LCC «Medicine-Inform», 2018)
Preconception preparation of patients with reccurent vulvovaginal candidiasis with the use of immunomodulation therapy I.O. Borovikov, A.S. Avetisian Kuban state medical university, Krasnodar, Russian Federation The article considers the experience of preconception preparation of patients with recurrent vulvovaginal candidiasis (RVVC). The paper describes clinical features of recurrent forms of candidiasis in women and the variant of treatment of this pathology in women planning pregnancy with a combination of systemic antimitotic and immunomodulating therapy with the assessment of the clinical and microbiological efficacy. Aim: assesssment of the efficacy of complex therapy with the use of a combination of systemic antimitotics and immunotropic medication Galavit® in preparation for pregnancy of women affected by recurrent vulvovaginal candidiasis. Patients and Methods: a comparative study was conducted including the results of treatment of 113 women affected by RVVC with pregnancy started within 6 months after the therapy and ended with the birth of a child: Group I (n=56) - Itraconazole; Group II (n=57) - Itraconazole + immunomodulation therapy with aminodihydrophthalasindione sodium (Galavit®). Diagnosis of infecting with Candida spp. was carried out by direct microscopy, seeding with the isolation of pure culture and the final identification of the pathogen. Results: it is established, that complex use of systemic antimitotic (itraconazole) and immunomodulator (Galavit) in the therapy of RVVC has 21,8±4,1% higher clinical and 12,6±3,5% higher microbiological efficacy. In 81.7% of women in Group I vulvovaginal candidiasis worsened during pregnancy, while in Group II, where a combination of Galavit® and antimycotic was used for pregravid preparation, only 28.3% of pregnant women had an exacerbation of VVC. The presence of ultrasound markers of intrauterine infection was detected in 56.7% of the pregnant women in Group I and in 18.3% in the Group II. Complicated births with premature discharge of amniotic fluid, abnormalities of labor in Group I were registered in 43.3% of cases, in group II - in 28.3%. The presence of signs of intrauterine infection was observed in 31.7% of the newborns in Group I and in 13.3% of newborns in Group II. Key words: recurrent vulvovaginal candidiasis, antimitotic, immunotrops therapy, preconception preparation, Galavit®. For citation: Borovikov I.O., Avetisian A.S. Preconception preparation of patients with reccurent vulvovaginal candidiasis with the use of immunomodulation therapy. Russian journal of Woman and Child Health. 2018;1(1):4-10.